Tantangan Dakwah Muhammadiyah di Era Digital - Muh Farhan Ali; Muh. Nur Rochim Maksum (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Islamic da'wah in the era of digital technology has undergone a major transformation with the presence of social media platforms such as Twitter, Instagram, and Facebook. Muhammadiyah, as one of the largest Islamic organizations in Indonesia, seeks to optimize digital media to spread Wasathiyah Islamic values more widely and quickly. The main challenge in digital da'wah is to ensure that the information conveyed remains accurate and does not cause misinformation. Haedar Nashir, Chairman of Muhammadiyah, emphasized the importance of combining fiqh on social media with public ethics, as well as involving the younger generation in digital da'wah to ensure that the message of da'wah remains relevant and acceptable to various levels of society. With an innovative and responsive strategy, Muhammadiyah da'wah is expected to be able to answer the challenges of the times while maintaining Islamic principles in facing the era of disruption.